2015
DOI: 10.1016/j.micpro.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Zero-load predictive model for performance analysis in deflection routing NoCs

Abstract: We study a static model for 2-D and 3-D networks that accurately represents the average distance travelled by packets under deflection routing, which is a specific form of adaptive routing. The model captures static properties of the network topology and the spatial distribution of traffic, but does not take into account traffic loading and congestion. Even though this static model cannot accurately predict packet latency under high load, we contend that it is a perfect predictor of deflection routing networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…The chaotic nature of deflections in bufferless routing makes the quest for an analytical model for deflection routing even more challenging. Previous work has identified that the most important parameter in bufferless networks is the mean distance between the source and destination node, based on the topology and the spatial distribution of traffic [21]. The authors demonstrate how this single metric can be used to compare candidate architectures.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…The chaotic nature of deflections in bufferless routing makes the quest for an analytical model for deflection routing even more challenging. Previous work has identified that the most important parameter in bufferless networks is the mean distance between the source and destination node, based on the topology and the spatial distribution of traffic [21]. The authors demonstrate how this single metric can be used to compare candidate architectures.…”
Section: Related Workmentioning
confidence: 99%
“…The reason is that the above approach, while surprisingly accurate and efficient, does not take into account the probabilistic and, therefore, difficult-to-predict nature of deflections. In fact, the authors in [21] state without exaggeration that "Due to the exceedingly complex spatial and temporal interference patterns of packets across the network in adaptive routing networks, an accurate analytic latency model seems to be out of reach". Simulation remains the only method for determining network latency under non-zero load conditions.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations